MANAGEMENT OF CRITICAL SPECIALIST WORKS IN MULTIPLE BRIDGE PROJECTS: A CASE STUDY - Sambu Potty, Narayanan; C.T, Ramanathan; Idrus, Arazi (2009)
This practical study identifies the critical specialist works at various stages of Design and Build (D&B) contracts and their influence on the successful delivery in multiple bridge projects. These specialist works become critical activities in multiple simultaneous projects environment. This may be due to lack of planning in the management of these critical specialist works. A case study of multiple bridge projects in Sabah, East Malaysia is considered. This study explains the process of optimisation in multiple projects to minimize the problems arising during the execution of specialist works (like temporary works, piling works and bridge beams) simultaneously. A study of the pre and post-implementation processes and lessons learned elicited from the experiences of those people managing these works in multiple project setup was done. Findings indicate that the optimization process of the specialist works will reduce the possibility or even prevent the specialist works from entering the critical zone. Recommendations are made on the scheduling practice and how to choose from the specialist works options while operating multiple simultaneous projects. Specialist work methods are determined based on analysis of various critical factors influencing the implementation process.